Genome-Wide Identification and Comparative Analysis of Albumin Family in Vertebrates. (16th June 2017) - Li, Shugang; Cao, Yiping; Geng, Fang
Albumins are the most well-known globular proteins, and the most typical representatives are the serum albumins. However, less attention was paid to the albumin family, except for the human and bovine serum albumin. To characterize the features of albumin family, we have mined all the putative albumin proteins from the available genome sequences. The results showed that albumin is widely distributed in vertebrates, but not present in the bacteria and archaea. The phylogenetic analysis of vertebrate albumin family implied an evolutionary relationship between members of serum albumin, α-fetoprotein, vitamin D–binding protein, and afamin. Meanwhile, a new member from the albumin family was found, namely, extracellular matrix protein 1. The structural analysis revealed that the motifs for forming the internal disulfide bonds are highly conserved in the albumin family, despite the low overall sequence identity across the family. The domain arrangement of albumin proteins indicated that most of vertebrate albumins contain 3 characteristic domains, arising from 2 evolutionary patterns. And a significant trend has been observed that the albumin proteins in higher vertebrate species tend to possess more characteristic domains. This study has provided the fundamental information required for achieving a better understanding of the albumin distribution, phylogenetic relationship, characteristic motif, structure, and new insights into the evolutionary pattern.